RESPONSE ANALYSIS: SCIENTIFIC ARTICLE WRITING TRAINING BASED ON INFORMATION LITERACY FOR STUDENTS AT HIGHER EDUCATION INSTITUTIONS - Alfianika, Ninit; Ridwan, Ridwan (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
The problem in this research is that students' skills in writing scientific articles are still weak. This research aims to analyze student responses by holding training in writing scientific articles based on information literacy. The type of research used is qualitative research using descriptive analysis methods. The instrument used in this research was an interview guide. The data sources in this research were 10 students of the Faculty of Tarbiyah and Teacher Training (FITK) of the Walisongo State Islamic University (UIN) Semarang. Data collection was carried out by conducting interviews with students regarding responses to information literacy-based scientific article writing training.  The research results showed that student responses were very positive when training in writing scientific articles based on information literacy was held. In general, students are interested, happy and willing to take part in information literacy-based scientific article writing training. The reason students take part in information literacy-based scientific article writing training is to increase their potential in writing articles; increasing information literacy through reading books and previous research journals; can produce your own work and share knowledge; improve and practice the ability to arrange words into sentences.